A randomized controlled trial of glycopyrrolate administered by metered dose inhaler in patients with uncontrolled asthma despite ICS/LABA treatment. (13th June 2022) - Kerwin, Edward; Dorinsky, Paul; Patel, Mehul; Rossman, Kimberly; Reisner, Colin; Maes, Andrea; Darken, Patrick; Griffis, Dianne; Fjällbrant, Harald
Abstract: Objective: To evaluate the efficacy and safety of three doses of glycopyrrolate metered dose inhaler (GP MDI) in patients with uncontrolled asthma despite treatment with inhaled corticosteroid/long-acting β2 -agonists (ICS/LABA) with or without tiotropium, to characterize the benefit of triple therapy. Method: This phase II/III, double-blind study randomized patients to 24 weeks' treatment with twice-daily GP MDI 36 µg, 18 µg, 9 µg, or placebo MDI (all delivered via Aerosphere inhalers), or once-daily open-label tiotropium 2.5 µg. Patients continued their own ICS/LABA regimen throughout the study. The primary endpoint was change from baseline in forced expiratory volume in 1 s (FEV1 ) area under the curve from 0 − 4 h (AUC0 − 4 ) at Week 24. Secondary endpoints included patient questionnaires to measure asthma control or symptoms. Safety was also assessed. Results: The primary analysis (modified intent-to-treat) population included 1066 patients. The primary study endpoint was not met (changes from baseline in FEV1 AUC0 − 4 at Week 24 were 294 mL, 284 mL, 308 mL, 240 mL, and 347 mL for GP MDI 36 µg, GP MDI 18 µg, GP MDI 9 µg, placebo, and open-label tiotropium, respectively). There were no significant differences between treatment and placebo in secondary endpoints at Week 24. Post-hoc analyses using post-bronchodilator FEV1 as the baseline measurement, or averaging values across multiple baseline visits, showed a dose-related response to GP MDI. The incidence of adverse events was low and similar across treatments. Conclusion: Although this study did not meet its primary endpoint, post hoc analyses identified a dose-related response to GP MDI when alternative definitions of baseline FEV1 were used in the analyses.